Pengaruh Brand Image dan Brand Awareness Terhadap Keputusan Pembelian Pizza Hut Delivery Cabang Plaju - Meilani, Windi; Rosa, Aslamia (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to analyze the effect of brand image and brand awareness on purchasing decisions for pizza hut delivery at the Plaju branch. This study used a quantitative approach with data collection methods through questionnaires. The population in this study were people in Palembang City aged 15-25 years who had purchased pizza hut delivery from the Plaju branch in October, November, December 2022 and January, February, March 2023. The sampling method used purposive sampling with a total sample of 100 respondent. Data analysis techniques in this study were hypothesis testing, coefficient of determination testing, and multiple linear analysis. the results of testing the calculated F value of 73,597 with a significance value of 0.000 (0.000 <0.05), brand image and brand awareness together have a positive and significant effect on purchasing decisions for Pizza Hut Delivey Plaju Branch. Keywords: Brand image, Brand Awareness, Purchase Decisions